Development of Interactive E-Module on Islamic Religious Education Subject Implementation of Independent Curriculum at Schools - Wahidah Ma’rifatunnisa’; Nurul Atik Hamida; Ruhaizan Baru (Edukasia Islamika : Jurnal Pendidikan Islam, 2022)
Students' lack of enthusiasm to participate in learning activities, especially in Islamic Religious Education subjects, is mainly caused by monotonous teaching materials. In addition, these teaching materials are considered not to support the learning process with the independent learning policy for students in the Independent curriculum. Therefore, teaching materials that meet the independent learning policy are needed, one of which is by using interactive e-modules. So this study aims to develop an interactive e-module for Islamic Religious Education to support the implementation of an independent curriculum for grade X SMKN 1 Lamongan, which can help teachers overcome problems when implementing an independent curriculum in the learning process of Islamic Religious Education. The development model used is the ADDIE model. The four stages in ADDIE development procedures are passed through five stages: Analysis, Design, Development, Implementation, and Evaluation. The data analysis technique calculates the percentage score of the validation assessment and user response. The study results show the development of interactive e-modules and the subject matter of the role of ulama' in spreading Islamic teachings in Indonesia, supporting the implementation of an independent curriculum. Those results met very valid criteria for display quality, software engineering, performance, interface, reusable, and maintainability, with a score of 98,77% in terms of IT. The score in terms of material gained 96,69%, and in terms of the media obtained a score of 98,56%. The results of students' and teachers' response tests from the results of the pretest before the interactive e-module implementation got a score of 69,54% and 74,66%. Then there was an increase in student scores in the posttest, with an average score of 89 compared to the pretest.